PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 81 PEKANBARU - Wahyuni, Fitri; Lazim N, Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is based on the low learning outcomes IPS of class students VA SD Negeri 81 Pekanbaru. The KKM determined by the school is 73. Of the 26 students, only 7 students (26,92%) attained the KKM, while the students who had not reached the KKM were 19 students (73,08%) with an average grade is 67,69. This study is aims to improve learning outcomes IPS of class VA SD Negeri 81 Pekanbaru by applying the model of learning cooperative, make a match’ type. Activity teachers on the first cycle of the first meeting obtained 66,7% with enough category, at the second meeting increased to 79,2% with good category. Furthermore, second cycle of the first meeting of teacher’s activity also increased to 83,3% with good category too and second cycle at the second meeting increased to 91,7% with very good category. While the activity of student in first cycle of first meeting get 62,5% with enough category, at second meeting of first cycle increased to 75% with enough category too. While in the first meeting of the second cycle of student activity increased to 83.3% with good category and at the second meeting of second cycle increased to 87.5% with very good category. Learning result data obtained from the average basic score is 67,69 which is increased to 16,48% with an average is 78,85 on the first cycle. On the second cycle increased to 23,57% with an average is 83,65. In the basic score of social sciences learning classical completeness students are 26,92% (not complete). After applied model of cooperative learning make a match’ type in first cycle of classical completeness of learning student increase with classical completeness is 76,92% and in second cycle classical completeness learning student increase again with classical mastery is 88,46%.Keywords: Cooperative learning model make a match type, learning outcomes IPS